PENERAPAN PENDIDIKAN KARAKTER DI SD - Rusmana, Adistia Oktafiani (Universitas Esa Unggul, 2019)
AbstractEducation is one of the main keys to building and shaping the quality of the character of citizens. The purpose of this study is the researcher wants to identify what good characters are shown by the students of SD Duri Kepa 03 and describe the application of character education in SDN Duri Kepa 03. The research method used is descriptive qualitative research method, so the results of this study are: 1) Character value that is applied and demonstrated that is religious, caring for the environment, responsibility, honesty and tolerance. 2) Application and concept of character education in Duri Kepa 03 Elementary School through habituation. 3). Strategies used by teachers in the application of character education such as always reminding students of good things, giving reprimands, giving examples or being role models, routine activities or habituation, and fostering student awareness. 4) Obstacles in the implementation of character education at SD Duri Kepa 03 are factors of teachers, parents, environment, and students. Ã‚Â Keywords:Character value, teacher strategy, inhibiting factorsÃ‚Â AbstrakPendidikan menjadi salah satu kunci utama membangun dan membentuk kualitas karakter warga negara. Tujuan dari penelitian ini adalah peneliti ingin mengidentifikasi karakter baik apa saja yang ditunjukan siswa SDN Duri Kepa 03 dan mendeskripsikan penerapan pendidikan karakter di SDN Duri Kepa 03. Metode penelitian yang digunakan menggunakan metode penelitian kualitatif deskriptif, sehingga hasil penelitian ini adalah: 1) Nilai karakter yang diterapkan dan ditunjukan yaitu religius, peduli lingkungan, tanggung jawab, jujur, dan toleransi. 2) Penerapan dan konsep pendidikan karakter di SDN Duri Kepa 03 melalui pembiasaan. 3).Strategi yang digunakan guru dalam penerapan pendidikan karakter seperti selalu mengingatkan siswa akan hal baik, memberikan teguran, memberikan contoh atau menjadi teladan, kegiatan rutin atau pembiasaan, dan menumbuhkan kesadaran siswa. 4) Hambatan dalam penerpan pendidikan karakter di SDN Duri Kepa 03 adalah faktor guru, orang tua, lingkungan, dan siswa.Ã‚Â Kata kunci:Nilai karakter, strategi guru, faktor penghambat